Missed Opportunities for Antifungal Stewardship during the COVID-19 Era - Brandon K. Hawkins; Samantha D. Walker; Mahmoud A. Shorman (MDPI AG, 2023)
Significant increases in antibacterial use were observed during the COVID-19 pandemic. However, subsequent analyses found this increase in antibiotic use to be excessive in comparison with the relatively low rates of bacterial coinfection. Although patients who are critically ill with COVID-19 may be at an increased risk for pulmonary aspergillosis, antifungal use in these populations remained underreported, particularly in later phases of the pandemic. This single-center, population-level cohort analysis compares the monthly use rates of mold-active antifungal drugs in the medical intensive care unit during April 2019-March 2020 (baseline) with those during April 2020-November 2022. The antifungal drugs included in the analysis were liposomal amphotericin B, anidulafungin, isavuconazonium, posaconazole, and voriconazole. We found that during 2020-2022, the usage of antifungal drugs was not significantly different from baseline for all included agents except isavuconazonium, which was used significantly more (p = 0.009). There were no changes in diagnostic modalities between the two time periods. The reported prevalence of and mortality from COVID-19-associated pulmonary aspergillosis (CAPA) may have resulted in higher rates of prescribing antifungal drugs for critically ill patients with COVID-19. Antimicrobial stewardship programs should develop and apply tools to facilitate more effective and appropriate antifungal use.